A Novel Copper-Binding Peptide That Self-Assembles Into a Transparent Antibacterial and Antiviral Coating - Boas, Daniel; Reches, Meital (Frontiers in Bioengineering and Biotechnology, 2021)
The health, economy, and quality of life all over the world are greatly affected by bacterial infections and viral outbreaks. Bacterial cells and viruses, such as influenza, can spread through contaminated surfaces and fomites. Therefore, a possible way to fight these pathogens is to utilize antibacterial and antiviral coatings, which reduce their numbers on contaminated surfaces. Here, we present a novel short peptide that can self-assemble, adhere to various surfaces, and bind different metal ions such as copper, which provides the surface with antibacterial and antiviral properties. For these functions, the peptide incorporates the amino acid 3,4-dihydroxyphenylalanine (DOPA), which provides the peptide with adhesive capabilities; a diphenylalanine motif that induces the self-assembly of the peptide; the metal-binding hexahistidine sequence. Our results demonstrate that the coating, which releases monovalent cuprous ions and hydrogen peroxide, provides the surfaces with significant antibacterial and antiviral properties. Additionally, the coating remains transparent, which is favorable for many objects and especially for display screens.